Modelling shifts in agroclimate and crop cultivar response under climate change. Issue 12 (30th September 2013) - Rötter, Reimund P.; Höhn, Jukka; Trnka, Mirek; Fronzek, Stefan; Carter, Timothy R.; Kahiluoto, Helena
Abstract: This paper aims: (i) to identify at national scale areas where crop yield formation is currently most prone to climate‐induced stresses, (ii) to evaluate how the severity of these stresses is likely to develop in time and space, and (iii) to appraise and quantify the performance of two strategies for adapting crop cultivation to a wide range of (uncertain) climate change projections. To this end we made use of extensive climate, crop, and soil data, and of two modelling tools: N‐AgriCLIM and the WOFOST crop simulation model. N‐AgriCLIM was developed for the automatic generation of indicators describing basic agroclimatic conditions and was applied over the whole of Finland. WOFOST was used to simulate detailed crop responses at four representative locations. N‐AgriCLIM calculations have been performed nationally for 3829 grid boxes at a 10 × 10 km resolution and for 32 climate scenarios. Ranges of projected shifts in indicator values for heat, drought and other crop‐relevant stresses across the scenarios vary widely – so do the spatial patterns of change. Overall, under reference climate the most risk‐prone areas for spring cereals are found in south‐west Finland, shifting to south‐east Finland towards the end of this century. Conditions for grass are likely to improve. WOFOST simulation results suggest that CO2 fertilization and adjusted sowing combined can lead to small yield increases of current barley cultivars under most climate scenarios on favourable soils, but not under extreme climate scenarios and poor soils. This information can be valuable for appraising alternative adaptation strategies. It facilitates the identification of regions in which climatic changes might be rapid or otherwise notable for crop production, requiring a more detailed evaluation of adaptation measures. The results also suggest that utilizing the diversity of cultivar responses seems beneficial given the high uncertainty in climate change projections. Abstract : Understanding the interactions of genotypes, management, climate and other environmental variables is instrumental for adaptation of crop production systems to climate change, but these are usually not taken into account in large area assessment approaches. To overcome this shortcoming a novel approach for assessing spatio‐temporal agroclimatic dynamics combined with crop simulations was developed and applied to exemplify its benefits using the case of shifting climatic risks to crop production in Finland. Benefits include the capabilities (i) to identify areas where crop yield is currently most prone to climate‐induced stresses, (ii) to evaluate how the severity of these stresses is likely to develop in time and space, and, (iii) to appraise and quantify the performance of alternative strategies for adapting crop cultivation to a wide range of climate change projections.